20 anos do Festival de Inverno da Universidade Federal de Minas Gerais: 1967 a 1986 - Fabricio Jose Fernandino (2011)
The present thesis discusses the fist initial 20 years of the Winter Festival of the Federal University of Minas Gerais (UFMG), addressing it under three aspects: the institution, the art and the community. It proposes the development and maintenance of transformative programs in the field of art and cultural production, from the perspective of the Festival lived experience. By means of the survey and analysis of the primary sources of the bibliographic production, news articles and journalistic publications, video documentaries, interviews, historical data and field experiments, it has been established a historical and reflexive view on the Winter Festival and it has been carried out an analysis to enable a critical view of the event relations in a straightforward relationship with the institution, the art and the community. These three aspects are approached on a year after year basis in different chapter corresponding to each year and built upon the researched data and its chronological development since the Festival inception in 1967 until 1986. The time period has been established as the initial 20 years of the event due to the aspect that these are the years that shaped and consolidated the UFMG Winter Festival in its basic structure. Categories of analysis have been elected to deal with the three aspects. For the institution, the categories elected are: proposals for the elaboration of the training program for university extension, cultural policies, policies to attract and foster the cultural development. In respect to the art, the categories are: conceptual propositions, transforming capacity, proposals for innovation and creative ramifications. Regarding the community, the categories covered are: formation of the public, relations with the community, interaction and dissociation from the public. This thesis reasserts the event importance that in its original features is a reference as a transforming cultural activity through the art. It has proved the effective transformative characteristic of the UFMG Winter Festival and the need to develop and maintain innovative programs in the field of art and cultural production based on the experience lived in the Winter Festival.